An experimental investigation of sharp force skeletal trauma with replica Bronze Age weapons. (February 2017) - Downing, MacKenzie; Fibiger, Linda
Abstract: Skeletal sharp force trauma provides direct evidence for the use of bladed weapons against humans. As such, it is an important source of evidence for examining the prevalence of violence and weapon use in the past. The primary aims of this study are to provide experimental evidence for the efficacy of Bronze Age weapons against skeletal tissue and to test the applicability of existing criteria for sharp force trauma analysis to Bronze Age skeletal material. To that end, three Bronze Age weapons - a dirk, flanged axe and Wilburton sword - were used to strike four Synbone spheres ('crania') and two cylinders ('long bones'). Subsequent damage to the weapons and Synbone was analyzed using macroscopic and microscopic methods including digital photography, three-dimensional digital modelling, and metric analysis. The results of the study suggest the Wilburton sword and flanged axe could be effective weapons in combat and existing methods for cutmark analysis are generally applicable to injuries created with Bronze Age weapons when taking into account the size of the weapons. Sword (slashing) and axe (chopping) trauma can be distinguished on the artificial bone material based on the degree of wastage and fracturing. Further research is needed to develop criteria for distinguishing sword and dirk trauma as sword trauma was not distinguishable from knife weapon classes. Additionally, Synbone may not be an ideal skeletal tissue analogue in sharp force trauma research as it does not record the microscopic striations created by a blade passing through bone. Highlights: Bronze Age Wilburton swords and flanged axes could have been effective weapons in combat. Existing criteria for cutmark analysis are applicable to Bronze Age sharp force trauma injuries. Synbone may not be an ideal skeletal tissue analogue in sharp force trauma research.